전해연마 용액에서 안정화 시간과 표면 거칠기에 따른 오스테나이트 스테인리스강의 전기화학적 특성 - 황현규; Hyun-kyu Hwang; 김성종; Seong-jong Kim (Corrosion science and technology, 2022)
The objective of this study was to investigate the electrochemical behavior and damage degree of metal surface under different conditions by performing a potentiodynamic polarization experiment using an electropolishing solution for UNS S31603 based on initial delay time and surface roughness (parameters). A second anodic peak occurred at initial delay time of 0s and 100s. However, it was not discovered at 1000s and 3600s. This research referred to an increase in current density due to hydrogen oxidation reaction among various hypotheses for the second anodic peak. After the experiment, both critical current density and corrosion current density decreased when the initial delay time (immersion time) was longer. As a result of surface analysis, characteristics of the potentiodynamic polarization behavior were similar with roughness, although the degree of damage was clearly different. With an increase in surface roughness value, the degree of surface damage was precisely observed. As such, electrochemical properties were different according to the immersion time in the electropolishing solution. To select electropolishing conditions such as applied current density, voltage, and immersion time, 1000s for initial delay time on the potentiodynamic polarization behavior was the most appropriate in this experiment.